Current diagnosis & treatment (Lange Medical Books/McGraw-Hill, 2006)
This is an excellent source of updated, authoritative, and concise information on diseases encountered in general surgery and the surgical subspecialties of otolaryngology, urology, gynecology, orthopedics, plastic and reconstructive surgery, and pediatrics....This is a wonderful resource for all levels of surgical practitioners as well as nonsurgical practitioners. In my experience, it has provided me with a framework to prepare for both oral and written boards. 3 Stars.